2017
DOI: 10.2139/ssrn.2997888
|View full text |Cite
|
Sign up to set email alerts
|

Strategy-Proofness of Stochastic Assignment Mechanisms

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…However, this result from the field can be driven by differences in the priority and cognitive ability of students. Moreover, Schmelzer (2018) found that subjects with very low and very high levels of contingent reasoning, as measured by choices in the two-person beauty contest game, are more likely to report truthfully in RSD and TTC than subjects with intermediate levels of contingent reasoning.…”
Section: Determinants Of Reporting Strategies: Biases Risk Aversionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this result from the field can be driven by differences in the priority and cognitive ability of students. Moreover, Schmelzer (2018) found that subjects with very low and very high levels of contingent reasoning, as measured by choices in the two-person beauty contest game, are more likely to report truthfully in RSD and TTC than subjects with intermediate levels of contingent reasoning.…”
Section: Determinants Of Reporting Strategies: Biases Risk Aversionmentioning
confidence: 95%
“…The main reason is probably that some of the mechanisms are not straightforward to understand, and the instructions for only one mechanism are already quite involved. However, there are two experimental papers (Schmelzer 2016(Schmelzer , 2018) that investigate subjects' preferences over mechanisms. Schmelzer (2016) studies DA with different tie-breaking rules for priorities.…”
Section: Preferences Over Mechanismsmentioning
confidence: 99%
“…When implemented via the usual sequential choosing procedure, SD is obviously strategyproof, while TTC has no obviously strategyproof implementation. Given that obvious strategyproofness increasingly appears to be a desirable property for practical application (Schmelzer, 2017;Troyan, 2019), it would be natural to consider the possibility of achieving it in conjunction with order symmetry. Zhou, Lin (1990).…”
Section: Discussionmentioning
confidence: 99%